Analisis Desain Perpustakaan Sekolah Pada Tingkat Budaya Literasi Siswa SMP Muhammadiyah 10 Surabaya - Asy'ari, Asy'ari (Universitas Muhammadiyah Surabaya, 2018)
This study aims to describe the library design on the interest of reading students SMP Muhammadiyah 10 class VII A. This study was conducted with a descriptive quantitative approach. The data were collected using questionnaires or questionnaires with relevant questions, then the data were analyzed descriptively through presentation by frequency divided by the number of respondents multiplied by 100%. The results are proven to library design has an important role to the students' reading interest so that the average design and facilities of library 2.86, the completeness of the 2.93 book collection and the library service are 2.71 with the total totals of 2.83. libraries have an important influence in increasing reading interest. So an attractive design that fits your reading needs will bring the reader to a fun atmosphere. Visible when students dioperpolis feel comfortable and happy tentuknya not separated from the interior layout of the room and laying open a neat and easy to find. At SMP Muhammadiyah 10 Surabaya continues to make improvements with design desaib tailored to the needs of students